Risk assessment and genetic counseling for Lynch syndrome – Practice resource of the National Society of Genetic Counselors and the Collaborative Group of the Americas on Inherited Gastrointestinal Cancer. Issue 3 (9th January 2022) - Holter, Spring; Hall, Michael J.; Hampel, Heather; Jasperson, Kory; Kupfer, Sonia S.; Larsen Haidle, Joy; Mork, Maureen E.; Palaniapppan, Selvi; Senter, Leigha; Stoffel, Elena M.; Weissman, Scott M.; Yurgelun, Matthew B.
Abstract: Identifying individuals who have Lynch syndrome involves a complex diagnostic workup that includes taking a detailed family history and a combination of various tests such as immunohistochemistry and/or molecular which may be germline and/or somatic. The National Society of Genetic Counselors and the Collaborative Group of the Americas on Inherited Gastrointestinal Cancer have come together to publish this practice resource for the evaluation of Lynch syndrome. The purpose of this practice resource was to provide guidance and a testing algorithm for Lynch syndrome as well as recommendations on when to offer testing. This practice resource does not replace a consultation with a genetics professional. This practice resource includes explanations in support of this and a summary of background data. While this practice resource is not intended to serve as a review of Lynch syndrome, it includes a discussion of background information and cites a number of key publications which should be reviewed for a more in‐depth understanding. This practice resource is intended for genetic counselors, geneticists, gastroenterologists, surgeons, medical oncologists, obstetricians and gynecologists, nurses, and other healthcare providers who evaluate patients for Lynch syndrome.